2017
DOI: 10.3390/ijms18091933
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Is a Critical Parameter for Chondrogenic Differentiation of Human Umbilical Cord Blood Mesenchymal Stem Cells in Type I/III Collagen Sponges

Abstract: Umbilical cord blood (UCB) is an attractive alternative to bone marrow for isolation of mesenchymal stem cells (MSCs) to treat articular cartilage defects. Here, we set out to determine the growth factors (bone morphogenetic protein 2 (BMP-2) and transforming growth factor-β (TGF-β1)) and oxygen tension effects during chondrogenesis of human UCB-MSCs for cartilage engineering. Chondrogenic differentiation was induced using 3D cultures in type I/III collagen sponges with chondrogenic factors in normoxia (21% O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 62 publications
5
32
0
1
Order By: Relevance
“…As previously reported, 3D-chondrogenesis of UCB-MSCs is more efficient when cultures are first placed in normoxia 62 , while hypoxia allows chondrocyte phenotype stabilization, as confirmed in our work by a down-regulation of the osteogenic and hypertrophic factor Alpl under hypoxia. Hypoxia stress at the beginning of the chondrogenesis probably imposes metabolic changes on UCB-MSCs, limiting ECM synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…As previously reported, 3D-chondrogenesis of UCB-MSCs is more efficient when cultures are first placed in normoxia 62 , while hypoxia allows chondrocyte phenotype stabilization, as confirmed in our work by a down-regulation of the osteogenic and hypertrophic factor Alpl under hypoxia. Hypoxia stress at the beginning of the chondrogenesis probably imposes metabolic changes on UCB-MSCs, limiting ECM synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…In other published studies, this trend was not observed for ACAN and COL2A1 for bioprinted chondrocytes [7]. In contrast, and as expected, ECM synthesis was more pronounced on D56 and the densitometry measurements after ECM staining confirmed the benefit of combining TGF-β1 and BMP-2 [75,[84][85][86][87]. As we previously reported in a study of synovial fluid MSCs, we observed no influence of BMP-2 alone on both gene and protein levels [37].…”
supporting
confidence: 84%
“…The differentiation of stem cells into chondrocytes involves multiple signaling pathways, such as TGF-β/BMP, Wnt/β-catenin and MaPKs (38)(39)(40). certain TGF-β superfamily members have been widely used to regulate cell differentiation by triggering a series of signaling cascades (41).…”
Section: Discussionmentioning
confidence: 99%